2015
DOI: 10.3342/ceo.2015.8.3.206
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Severe to Profound Idiopathic Sudden Sensorineural Hearing Loss

Abstract: ObjectivesWhile a severe to profound sudden sensorineural hearing loss (SSNHL) may cause serious disability in verbal communication, there have been little studies focusing on this high degree SSNHL. The present study was aimed to investigate the characteristics of hearing recovery in a high degree SSNHL (>70 dB).MethodsThree hundred and two SSNHL patients were enrolled. For a long-term follow-up, 46 patients were evaluated. Hearing level was examined by pure tone audiometry on day 1, week 3, month 3, month 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Previous research on prognostic factors for SSNHL found that initial severe hearing loss, old age, presence of vertigo, a downward audiogram pattern, late onset of treatment, and a decreased score for speech discrimination were poor prognostic indicators in SSNHL . There has been increased interest in evaluating the role of various cardiovascular risk factors in SSNHL, and high fibrinogen levels, high white blood cell counts, and high LDL cholesterol values have all been shown to correlate with poorer hearing recovery .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on prognostic factors for SSNHL found that initial severe hearing loss, old age, presence of vertigo, a downward audiogram pattern, late onset of treatment, and a decreased score for speech discrimination were poor prognostic indicators in SSNHL . There has been increased interest in evaluating the role of various cardiovascular risk factors in SSNHL, and high fibrinogen levels, high white blood cell counts, and high LDL cholesterol values have all been shown to correlate with poorer hearing recovery .…”
Section: Discussionmentioning
confidence: 99%
“…Over half of the people who experience SSNHL will undergo spontaneous partial or complete hearing recovery; nevertheless, bilateral symptoms, profound hearing loss, advanced age, and delays in treatment are negative prognostic factors ( Sara et al, 2014 ; Edizer et al, 2015 ). If recovery is not achieved within 3 months after the onset of SSNHL, studies support that cochlear implantation may be beneficial in regaining hearing and reduction of SSNHL-associated tinnitus ( Ramos et al, 2012 ; Blasco and Redleaf, 2014 ; Jo et al, 2015 ; Dagna et al, 2016 ).…”
Section: And Acquired Hearing Lossmentioning
confidence: 99%
“…In our case, WCT improved the feeling of fullness after the first session and improved hearing loss, tinnitus, and dizziness after the completion of the WCT treatment regime (12 weeks). The observed effects of our case are unlikely to be due to steroid treatment because of the deterioration of the patient's hearing after treatment or due to the natural course of SSNHL and natural recovery since spontaneous recovery is usually within weeks of SSNHL [16]. In this case, we cannot give clear explanations as to how a complementary treatment, such as WCT, improved the patient's symptoms.…”
Section: Discussionmentioning
confidence: 72%